FEATURES OF INFLUENCE OF PUBLIC AUTHORITIES ON CIVIL SOCIETY IN THE CONTEXT OF MANAGEMENT IN THE RUSSIAN FEDERATION - M. Yakovleva (Вестник университета, 2018)
The interaction of civil society with public authorities in Russia has been studied. The main types of impacts in public administration in the Russian Federation, and, in particular, determines the ways of public authorities ‘ impact on civil society within the governance process has been analyded. The article considers the models of interaction between public authorities and civil society structures typical for the Russian Federation. The conclusion that there is not only the impact of public authorities on civil society, but also that this inuence is mutual is substantiated.